Sea Level Rise of Sumatera Waters based on Multi-Satellite Altimetry Data - Isna Uswatun Khasanah (Indonesian Journal of Geography, 2018)
The information of sea level rise was needed in the Indonesia as archipelago country to management risk and development coastal area. This research study took in West Sumatra waters, because the majority people have lived in coastal area and some areas is located below 100 m above Mean Sea Level (MSL). The sea level data was taken from multi-satellite altimetry, they are Topex/Poseidon, Jason-1, and Jason-2. The period of data started from 1993 until 2015.Preliminary data processing of satellite altimetry was done by global test and post-processing of satellite altimetry data. The sea level rise analysis done by linear regression methods. Linear regression formula of sea level rise in West Sumatra Waters during the period was  y = 1.586 + 0.0000113x. The change of sea level during period 1993 until 2015 was 3.394 cm with mean sea level rise value was 1.35 mm/year